2014
DOI: 10.1038/cmi.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

Over-activation of TLR5 signaling by high-dose flagellin induces liver injury in mice

Abstract: Flagellin is a potent activator of a broad range of cell types that are involved in innate and adaptive immunity. Therefore, it is a good adjuvant candidate for vaccines, and it might function as a biological protectant against both major acute radiation syndrome during cancer radiotherapy and a mitigator of radiation emergencies. However, accumulating evidence has implicated flagellin in the occurrence of some inflammatory diseases, such as acute lung inflammation, cardiovascular collapse and inflammatory bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 49 publications
2
70
0
1
Order By: Relevance
“…27 Briefly, spleens were obtained from 6-to 8-week-old female C57BL/6 mice, smashed using syringe pistons in phosphate-buffered saline Stimulating macrophages with flagellin It had been reported that LPS pretreatment of macrophages allowed a robust IL-1b released. So, macrophages were pretreated with 50 ng/ml LPS for 3 h, and then stimulated with flagellin using or no using DOTAP transfection (Roche Diagnostics, BASEL, Switzerland).…”
Section: Animalsmentioning
confidence: 99%
“…27 Briefly, spleens were obtained from 6-to 8-week-old female C57BL/6 mice, smashed using syringe pistons in phosphate-buffered saline Stimulating macrophages with flagellin It had been reported that LPS pretreatment of macrophages allowed a robust IL-1b released. So, macrophages were pretreated with 50 ng/ml LPS for 3 h, and then stimulated with flagellin using or no using DOTAP transfection (Roche Diagnostics, BASEL, Switzerland).…”
Section: Animalsmentioning
confidence: 99%
“…Additionally, Neely et al showed that administering a single low dose of flagellin in a murine model of burn injury and infection restored neutrophil response increasing bacterial clearance [12]. In contrast, others studies have shown that flagellin can induce pathophysiological inflammation that causes tissue damage [5, 9, 10, 13], a condition we have termed as flagellemia. Neutralization of flagellin can attenuate systemic inflammatory responses [14].…”
Section: Introductionmentioning
confidence: 99%
“…Neutralization of flagellin can attenuate systemic inflammatory responses [14]. We, as well as others, have reported that flagellin is an active contributor to pathophysiological responses such as sepsis [5, 9, 10, 12, 15, 16], liver injury [13], pulmonary inflammation and cardiovascular damage [9, 16, 17, 18]. We recently reported that luminal flagellin is internalized by human IECs [6], followed by dissemination into the systemic circulation under various pathophysiological conditions including burn injury [19, 20] and inflammatory bowel disease (IBD) [2124].…”
Section: Introductionmentioning
confidence: 99%
“…27 Briefly, spleens were obtained from 6-to 8-week-old female C57BL/6 mice, smashed using syringe pistons in phosphate-buffered saline NLRC4 activating reduces the immune responses against FliC W Li et al…”
Section: Animalsmentioning
confidence: 99%
“…So, macrophages were pretreated with 50 ng/ml LPS for 3 h, and then stimulated with flagellin using or no using DOTAP transfection (Roche Diagnostics, BASEL, Switzerland). 27,29 Briefly, 15 ml of DOTAP liposomal transfection reagent was incubated with 5 mg of purified flagellin for 20 min in serum-free media, and then 1 ml of RPMI 1640 medium was added. For no DOTAP transfection, 100 nM flagellin was added to macrophages directly in a 96-well plate, and supernatants were collected after 6 h to measure IL-1b and IL-18 levels.…”
Section: Stimulating Macrophages With Flagellinmentioning
confidence: 99%